ASUHAN KEPERAWATAN KLIEN HERNIA INGUINALIS DI PAVILIUN MAWAR RSUD JOMBANG - Dyah Hanum Pertiwi; Siti Muniroh; Nurul Khoirun Nisa (Universitas Pesantren Tinggi Darul Ulum, 2020)
Abstract Inguinal hernia is a condition in which intra-abdominal fat protrudes through the weak part of the lower abdominal muscles. Caused by congenital, obesity, pregnancy, straining, chronic coughing and clients who work as physical workers, strenuous physical activity results in a continuous increase in pressure on the intra-abdominal muscles, thus triggering the protrusion of organs through the walls of weak organs. This study aims to conduct a study of Nursing Care literature on Inguinal Hernia clients. This research method the study of literature in the scientific papers of diploma nursing study program at the Faculty of Health Science, Unipdu Jombang in 2016-2018 which includes assessment analysis, diagnosis determination, intervention, implementation, and evaluation in several research units. The results of the literature study found that pain priority problems with different scales, in post-operative clients, there were pain and risk of infection problems, after the nursing action was carried out for 3x24 hours of pain and the risk of infection experienced by clients decreased. There are differences regarding the etiology of 4 clients. As such, efforts are made to prevent inguinal hernias from reducing the activity of lifting heavy loads, maintaining ideal body weight, eating foods high in fiber to prevent constipation. Keywords : Nursing care, hernia,intra-abdominal muscles.